2005
DOI: 10.1038/sj.ejhg.5201360
|View full text |Cite
|
Sign up to set email alerts
|

Cascade testing in familial hypercholesterolaemia: how should family members be contacted?

Abstract: Cascade testing or screening provides an important mechanism for identifying people at risk of a genetic condition. For some autosomal dominant conditions, such as Familial Hpercholesterolaemia (FH), identifying relatives allows for significant health-affecting interventions to be administered, which can extend a person's life expectancy significantly. However, cascade screening is not without ethical implications. In this paper, we examine one ethically contentious aspect of cascade screening programmes, name… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
88
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(89 citation statements)
references
References 32 publications
0
88
1
Order By: Relevance
“…Gauging index patients' preferences about the method of familial cascading is important given the continuing debate about whether clinicians should contact family members directly to disclose genetic information and inform them about the opportunity for predictive testing (Offit et al 2004;Newson and Humphries 2005). Empirical research suggests that direct contact by a member of the clinical team maximises the numbers of family members coming forward for FH screening (Umans-Eckenhausen et al 2001;Hadfield et al 2009); however, it also raises ethical issues.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Gauging index patients' preferences about the method of familial cascading is important given the continuing debate about whether clinicians should contact family members directly to disclose genetic information and inform them about the opportunity for predictive testing (Offit et al 2004;Newson and Humphries 2005). Empirical research suggests that direct contact by a member of the clinical team maximises the numbers of family members coming forward for FH screening (Umans-Eckenhausen et al 2001;Hadfield et al 2009); however, it also raises ethical issues.…”
Section: Discussionmentioning
confidence: 99%
“…For example, an earlier Dutch study of FH cascading reported that 20% of family members approached reported feeling under pressure to have DNA testing following direct clinical contact (van Maarle et al 2001). The ethico-legal debate about disclosure of genetic information by clinicians frequently focuses upon breaches of confidentiality and patients' right to privacy versus family members' right to know genetic information about themselves and be informed about testing/treatment option (Newson and Humphries 2005;Leonard and Newson 2010;Skene and Forrest 2010). This study, like that reported by Horstman and Smand (2008), suggests that index patients may be less worried about their own and/or relatives' privacy than ensuring that their relatives are not made unduly anxious by unsolicited approaches from the clinical team.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…8,9 There has been some discussion on how to cascade information about genetic health risks to the relatives of patients with familial hyper-cholesterolaemia, including the active contacting of relatives directly by professionals, although this depends entirely upon information provided by the proband. 10 With genetic diseases increasingly treatable and preventable, some recommend a more proactive role of genetic professionals. 11,12 A potential obstacle to professional encouragement of family communication may be too great a respect for the principle of nondirectiveness, when understood as the rather unhelpful notion of simply having to give the patient what they ask for.…”
Section: Introductionmentioning
confidence: 99%